Synthesis of some Schiff's bases derivatives from aminoazo compounds (Baghdad Science Journal, 2007)
Reaction of,2- [( 4- amio phenyl ) diazenyl] 1,3,4- thiadiazole -5- thiol (S1) with p- chlorobenzeldehyde,3,4 – dimethoxy benzaldehyde and pyrrol-2- carbonxaldehyde gave -5- [{4-(4-chlorobenzylidene amino) phenyl} diezenyl]-1,3,4- thiadiazole-2- thiol (S2),5-[{ 4-[(3,4- dimethoxybenzyldene )amino phenyl ] diazenyl)-1,3,4- thiadiazole-2-thiol,(S3) and -5- [4-(1,H – pyrrol -2- yl- methylene)amino phenyl] diazenyl)-1,3,4- thiadiazole-2- thiol (S4) respectively as schiff's bases compounds. On the same route-2-[(4-amino-1- naphthyl ) diazenyl] -1,3,4- thiadiazole -5- thiol (S5) reacts with –p- chloro benzaldehyde and –m- nitrobenzaldehyde to give the follwing schiff's bases -5-[{ 4-(4- chloro benzylidene ) amino -1- naphthyl} diazenyl] -1,3,4- thiadiazole -2- thiol (S6) and -5- ({ 4- [3- nitrobenzylidene) amino] -1- naphthyl({ diazenyl) -1,3,4 – thiadiazole-2- thiol (S7). Sn2 reaction was carried out by the reaction of compound (S6,S7) with bromo ethyl acetate to get ethyl[5{4-(4- chlorobenzylidene amino)-1- naphthyl} diazenyl] -1- 1,3,4- thiadiazole-2- yl- thio] acetate (S8) and ethyl [5-{4- (2- nitrobenzylidene amino)-1- naphthyl diazenyl] -1,3,4- thiadiazole -2-yl-acetate (S9).(Fig.1).